2009
DOI: 10.1111/j.1365-2109.2009.02436.x
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitory compound produced byPseudomonaswith effectiveness onVibrio harveyi

Abstract: Persistence of the antivibrio property of the potential antagonistic probiotics, Pseudomonas MCCB 102 and 103, at di¡erent temperatures, pH and in organic solvents was studied. The antivibrio compound was extracted, puri¢ed and characterized using thin-layer chromatography, high-pressure liquid chromatography, liquid chromatography-mass spectroscopy, UVV is and nuclear magnetic resonance spectroscopy and identi¢ed as N-methyl-1-hydroxyphenazine, a phenazine antibiotic. The toxicity of the compound was tested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 26 publications
3
24
3
Order By: Relevance
“…Studies on the application of haemocyte culture or any other primary cultures of shrimp in cytototoxicity and especially the genotoxicity of drugs, management chemicals and pollutants in aquaculture systems have been rarely cited in literature. The P. monodon heamocyte culture has been applied for assessing cytotoxicity of N-methyl-1-hydroxyphenazine, a proposed aquaculture drug (Preetha et al, 2010) and benzalkonium chloride, an aquaculture management chemical employing MTT assay. Sung et al (2003) examined the effects and toxicity of phthalate esters on the isolated haemocytes of Macrobrachium rosenbergii utilising haemocytic adhesion, pseudopodia formation, superoxide anion production and phenoloxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the application of haemocyte culture or any other primary cultures of shrimp in cytototoxicity and especially the genotoxicity of drugs, management chemicals and pollutants in aquaculture systems have been rarely cited in literature. The P. monodon heamocyte culture has been applied for assessing cytotoxicity of N-methyl-1-hydroxyphenazine, a proposed aquaculture drug (Preetha et al, 2010) and benzalkonium chloride, an aquaculture management chemical employing MTT assay. Sung et al (2003) examined the effects and toxicity of phthalate esters on the isolated haemocytes of Macrobrachium rosenbergii utilising haemocytic adhesion, pseudopodia formation, superoxide anion production and phenoloxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity assessments in brine shrimp showed pyocyanin to be non-toxic at concentrations up to 100 mg/L, and the LC 50 values were (296.65依18.15) mg/ L and (215.312依35.660) mg/L for the exposure times of 12 h and 24 h respectively. The cytotoxicity (IC 50 ) of pyocyanin from environmental isolates of P. aeruginosa in primary haemocyte cultures from Penaeus monodon was found to be (1.40依0.31) mg/L, and on V. harveyi at 0.5 mg/L, it showed static effect and cidal at 1.0 mg/L [16] . NMR spectroscopic study confirmed that the extracted compound, antagonistic to Vibrio, was pyocyanin.…”
Section: Discussionmentioning
confidence: 99%
“…Pyocyanin produced from environmental isolate of P. aeruginosa has been identified as the key molecule that inhibits growth of vibrios in aquaculture systems [16] . It has also been demonstrated that environmental isolate of Pseudomonas can control vibrios and improve larval survival in shrimp hatchery systems [15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Alavandi et al 2004;Preetha et al 2009). Therefore, exploring for new bioactive compounds against shrimp bacterial disease agents like V. harveyi is an urgent priority.…”
Section: Introductionmentioning
confidence: 97%